Macro-networks: an application to the euro area financial accounts - Olli Castrén; Michela Rancan (European Central Bank (ECB), 2013)
We use financial accounts data at sector level to construct financial networks for individual euro area countries. We then connect the country-level networks to one large “Macro Network”, using information on cross-border linkages between the national banking sectors. We then evaluate the features of the resulting framework using various network statistics. Shock simulations reveal that the structural features of the bilateral linkages are a key determinant of the losses that may be generated when the shocks propagate in the system. The network structures evolve over time, showing increasing interconnectedness in different instrument categories before the financial crisis hit in 2007, and a sharp retrenchment from bilateral exposures after the crisis started. This reflects the surge in counterparty risk and the de-leveraging processes which were triggered by the initial asset price losses and were further amplified by the economic downturn. As a consequence, there was a marked deterioration in financial integration both within economies and across countries in the euro area. Nonetheless, our analysis suggests that the risk of contagion is not reduced, while a more diversified portfolio of cross-border exposures might mitigate shocks effects.
Keywords: E44; F36; G01; G15; G21; 330; Balance sheet contagion; cross-border exposures; Financial crises; Financial networks; interconnectedness